Epigenetics and Epigenomics - Payne, Christopher J. (IntechOpen, 2014)
The book aims to provide an overview of current knowledge regarding epigenetics and epigenomics. Included are reviews on the role of epigenetics in the development and pathogenesis of the vascular endothelium and nervous system, as well as our current understanding of the potential etiologies of Autism Spectrum Disorders. Additional chapters are devoted to DNA methylation, genomic imprinting and human reproduction. A discussion of the role of the epigenome in cancer prevention and polyphenols is also included. Authors provide research findings from both human data and animal model studies. This book will be of interest to scientists, physicians and lay readers wishing to review recent developments in the field of epigenetics and epigenomics.